2006
DOI: 10.1093/fampra/cml026
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomized trial of a multifaceted primary care decision-support intervention for inherited breast cancer risk

Abstract: No convincing evidence of the effectiveness of the intervention was found, probably reflecting barriers to its use in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 23 publications
0
63
0
Order By: Relevance
“…using the Cochrane Collaboration's tool for assessing risk of bias 21 (Table 2). [22][23][24][25][26][27][28][29][30][31] The heterogeneity of interventions and outcomes precluded any meta-analysis of the data. The review provides a narrative synthesis of the data.…”
Section: Study Appraisal and Synthesis Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…using the Cochrane Collaboration's tool for assessing risk of bias 21 (Table 2). [22][23][24][25][26][27][28][29][30][31] The heterogeneity of interventions and outcomes precluded any meta-analysis of the data. The review provides a narrative synthesis of the data.…”
Section: Study Appraisal and Synthesis Methodsmentioning
confidence: 99%
“…Women in the cervical screening trial had a greater understanding of screening guidelines and, in particular, screening intervals recommended for cervical screening as a result of the intervention. 32 Wilson et al 29 found no differences in patient knowledge between groups despite patient and clinician education.…”
Section: Patient Knowledgementioning
confidence: 98%
See 3 more Smart Citations